Gastrin-releasing peptide receptors in the central nervous system: role in brain function and as a drug target - Roesler, Rafael; Schwartsmann, Gilberto (Frontiers in Endocrinology, 2012)
Neuropeptides acting on specific cell membrane receptors of the G protein-coupled receptor (GPCR) superfamily regulate a range of important aspects of nervous and neuroendocrine function. Gastrin-releasing peptide (GRP) is a mammalian neuropeptide that binds to the GRP receptor (GRPR, BB2). Increasing evidence indicates that GRPR-mediated signaling in the central nervous system (CNS) plays an important role in regulating brain function, including aspects related to emotional responses, social interaction, memory, and feeding behavior. In addition, some alterations in GRP or GRPR expression or function have been described in patients with neurodegenerative, neurodevelopmental, and psychiatric disorders, as well as in brain tumors. Findings from preclinical models are consistent with the view that the GRPR might play a role in brain disorders, and raise the possibility that GRPR agonists might ameliorate cognitive and social deficits associated with neurological diseases, while antagonists may reduce anxiety and inhibit the growth of some types of brain cancer. Further preclinical and translational studies evaluating the potential therapeutic effects of GRPR ligands are warranted.